The Romance of Revenge: An Alternative History of Jeffrey Dahmer's Trial - Gross, Samuel R. (1995)
On Feb. 17, 1992, Jeffrey Dahmer was sentenced to fifteen consecutive terms of life imprisonment for killing and dismembering fifteen young men and boys. Dahmer had been arrested six months earlier, on July 22, 1991. On Jan. 13 he pled guilty to the fifteen murder counts against him, leaving open only the issue of his sanity. Jury selection began two weeks later, and the trial proper started on Jan. 30. The jury heard two weeks of horrifying testimony about murder, mutilation and necrophilia; they deliberated for five hours before finding that Dahmer was sane when he committed thos crimes. After the verdict, a minister who had counselled members of the victims' families told the Chicago Tribune, I think this will be the beginning of a healing. At his sentencing two days later, Dahmer said, I take all the blame for what I did... Your honor, it is over now. This has never been a case of trying to get free. I never wanted freedom. His lawyer told the press that no appeal was planned. What happened after Dahmer's arrest is of minor importance by comparison with what he did, which is unspeakable. Still, the criminal justice system did very well in this case. It handled a revolting set of crimes and a potentially explosive trial with as much civility, compassion, and dispatch as possible. Half a year after the arrest, the trial was truly over, and, let us hope, the healing did begin. Jeffrey Dahmer was tried in Wisconsin - one of the fourteen American states that have no death penalty. How would this drama play in one of the thirty-six other states? He would certainly be charged with capital murder, and then a new set of horrors would begin